Analisis Faktor-Faktor yang Memengaruhi Profitabilitas di PT Bank Syariah Indonesia Tbk Tahun 2018-2023 - Riska Fitriani; Khairul Alim (Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
The primary measure of Bank Syariah Indonesia's success in its mission to compete on a worldwide scale is the company's performance.  Credibility and public curiosity are piqued by good performance.  Customers are more likely to have faith in a bank with a high Return On Assets (ROA), which measures how profitable the institution is.  In order to determine what factors affect ROA, this research will look at the following ratios: Capital Adequacy Ratio (CAR), Operating Expenses to Operating Income (BOPO), Non-Performing Financing (NPF), and Financing to Deposit Ratio (FDR).  This study makes use of secondary data culled from Bank Syariah Indonesia's quarterly financial reports covering the years 2018–2023.  Multiple liear regression was used to carry out the study.  According to the findings, ROA is considerably impacted by CAR, BOPO, NPF, and FDR all at once.  Partially, however, CAR and FDR do not affect ROA much, although BOPO and NPF do.